Lagu Nasional: Sarana Retorika Ideologi Kebangsaan - Yulius Rizki Hutagaol; Ziko Rizky Prabowo; Muhammad Rafli Pradanto; Ovan Bagus Jatmika (Institut Seni Indonesia Denpasar, 2021)
Purpose: The study aims to discuss the role of the lyric (verbal) and music (non-verbal) aspects in the national anthem as a means of rhetoric for the national ideology (in this case the ideology of the Indonesian nation). Research methods: The method used is qualitative which is more specifically under the umbrella of phenomenological research. Results and discussion: The author chooses the song